Yogmaya and Durga Devi: Different Modes of Resistance to Patriarchy - Lama, Kumari (The Outlook: Journal of English Studies, 2021)
This paper analyses Yogmaya and Durga Devi’s modes of resistance against Brahmanic rigidity in Nepali society a century ago. It is based on Barbara Nimri Aziz’s Yogmaya & Durga Devi: Rebel Women of Nepal (2020). Yogmaya and Durg Devi have resisted against Hindu patriarchal orthodoxy that has inflicted immense structural domination on women and validated various social injustices. Yogmaya has taken path of religion and spirituality, whereas Durga Devi fetches justice to victims through law. Hindu values were extremely rigid towards women that burning sati, child marriage, and widow system used to be the part of their life. Amidst patriarchal austerity these daring women raise their voice for social reforms taking distinct paths of resistance. Nonetheless, both voice against women’s violence, corruption, and social injustices caused by Hindu authoritarian rules and religious fanaticism. This paper examines Yogmaya and Durga Devi’s contrasting modes of resistance against Hindu patriarchal domination employing Judith Butler’s perspective on patriarchal normative heterosexuality that treats several bodies including women as ‘unlivable’ and Margaret S. Archer’s idea of resistance and human agency as fundamental theoretical backing.